Pengetahuan, Sikap, Gaya Hidup Remaja, dan Peran Keluarga terhadap Perilaku Seks Pranikah - Pangaribuan, Santa Maria; Barus, Vivi Ana; Siringoringo, Lince (Poltekkes Kemenkes Tanjung Karang, 2022)
Premarital sex behavior is the most prominent adolescent issue and leads to many unwanted consequences such as abortion, dropout, premarital pregnancy, sexually transmitted diseases, and HIV / AIDS. Adolescents with good knowledge, good attitudes, good supporting family, and a good lifestyle will tend to stay away from premarital sex behavior. The purpose of this study was to determine the knowledge, attitudes, lifestyle of adolescents, and the role of the family regarding premarital sex behavior in Talimbaru Village, Barusjahe District, Karo Regency. This quantitative research used a cross-sectional design. The research subjects were adolescence aged 12-24 years, totaling 74 respondents. The instruments used in data collection were demographic data, knowledge scale, attitude scale, lifestyle scale, and family role scale. The results showed that: 59.5% of respondents have good knowledge, 55.4% of respondents have good attitudes, 81.1% of respondents have good influence from their families, and 55.4% of respondents have a good lifestyle. Based on the results, it is important coaching (through government counseling programs, training, and extracurricular activities) about reproductive health issues, especially sexuality by developing more effective ways and methods so that teenagers stay alert and avoid deviant behaviors including premarital sexual behavior. Nurses can also create a promotion program on the topic of communication for parents and teenagers